A new species of Pagurixus (Crustacea: Decapoda: Anomura: Paguridae) from Southern Japan - Komai, Tomoyuki; Myorin, Eijieiji (Zootaxa, 2005)
A new hermit crab species of the pagurid genus Pagurixus Melin, P. fasciatus, is described from shallow rocky reefs of Japan. Fifteen congeners are known from the Indo-Pacific region. The new species is most similar to P. handrecki Gunn & Morgan, known from Western and southeastern Australia, but can be distinguished from the latter by the less setose antennal acicle, the dorsomesial margin of the right palm which is sharply carinate along the entire length, the fewer ventral spines on the ambulatory dactyli, and the sharp, smooth dorsolateral carina of the female right palm. Coloration in life is also different between the two species.